Perjodohan dan Resistensi Perempuan dalam Metropop Summer Sky Karya Stephanie Zen - Tania Intan (SUAR BETANG, 2020)
Matchmaking or marriage arrangement is an unpopular phenomenon in the feminist view since it is considered to be detrimental to women. However, matchmaking still occur in contemporary context as as shown in a number of contemporary Indonesian literary works. The difference is, when compared to female characters who lived in the past such as Siti Nurbaya by Marah Roesli or Midah Si Manis Bergigi Emas by Pramoedya Ananta Toer, women in contemporary literary works such as metropop and chick-lit have had space to show resistance to matchmaking happened to them. This study aims to examine the phenomenon of matchmaking and women's resistance in Stephanie Zen's novel Summer Sky, which is the object of research. The method used is descriptive qualitative method. The analysis was carried out with the sociology of literature approach and feminist literature studies with O'Brien and Randall matchmaking theoretical foundation, as well as Barker's theory of resistance. This study shows that the parents in the novel act as facilitators in finding a partners, while the decision to have a relationship is the decision of each individual as an adult. The matchmaking patterns filfills four stages of interaction, namely physical encounters, awareness of the existence of a potential partner, same emotional state, and marriage as a representation of a common goal. There is no significant resistance from the female protagonist because of compatibility factor with her partner and there is no coercion from parents. Therefore, despite the theme of matchmaking, the novel Summer Sky is presented like a love story in general.AbstrakPerjodohan merupakan fenomena yang tidak populer dalam pandangan feminis karena dianggap cenderung merugikan perempuan. Namun demikian, perjodohan masih saja terjadi dalam konteks kekinian sebagaimana ditampilkan dalam sejumlah karya sastra kontemporer Indonesia. Hal yang membedakan, bila dibandingkan dengan tokoh perempuan yang hidup di masa lampau seperti Siti Nurbayakarya Marah Roesli atau tokoh MidahSi Manis Bergigi Emaskarya Pramoedya Ananta Toer, perempuan modern telah memiliki ruang untuk menunjukkan resistensi atas perjodohan yang menimpanya. Kondisi ini tergambar dalam novel metropop Summer Skykarya Stephanie Zen yang menjadi objek penelitian. Analisis dilakukan dengan pendekatan sosiologi sastra dan kajian sastra feminis. Kajian ini menunjukkan bahwa dalam novel tersebut, orang tua hanya membantu mencarikan pasangan dan keputusan untuk menjalin hubungan merupakan keputusan masing-masing individu sebagai pribadi dewasa. Empat tahap interaksi yang dikemukakan Randall terpenuhi, yaitu pertemuan fisik, saling menyadari keberadaan, berada dalam situasi emosi yang sama, dan adanya simbol yang mewakili fokus bersama.